Retrieval practice improves memory in patients with schizophrenia: new perspectives for cognitive remediation - Camille Jantzi; Amaury C. Mengin; David Serfaty; Elisabeth Bacon; Julien Elowe; François Severac; Nicolas Meyer; Fabrice Berna; Pierre Vidailhet (BMC Psychiatry, 2019)
Abstract Background Schizophrenia is associated with severe cognitive deficits, particularly episodic memory deficits, that interfere with patients’ socio-professional functioning. Retrieval practice (also known as testing effect) is a well-established episodic memory strategy that involves taking an initial memory test on a previously learned material. Testing later produces robust long-term memory improvements in comparison to the restudy of the same material both in healthy subjects and in some clinical populations with memory deficits. While retrieval practice might represent a relevant cognitive remediation strategy in patients with schizophrenia, studies using optimal procedures to explore the benefits of retrieval practice in this population are still lacking. Therefore, the purpose of our study was to investigate the benefits of retrieval practice in patients with schizophrenia. Methods Nineteen stabilised outpatients with schizophrenia (DSM-5 criteria) and 20 healthy controls first studied a list of 60 word-pairs (30 pairs with weak semantic association and 30 non associated pairs). Half the pairs were studied again (restudy condition), while only the first word of the pair was presented and the subject had to recall the second word for the other half (retrieval practice condition). The final memory test consisted in a cued-recall which took place 2 days later. Statistical analyses were performed using Bayesian methods. Results Cognitive performances were globally altered in patients. However, in both groups, memory performances for word-pairs were significantly better after retrieval practice than after restudy (56.1% vs 35.7%, respectively, Pr(RP > RS) > 0.999), and when a weak semantic association was present (64.7% vs 27.1%, respectively; Pr(weak > no) > 0.999). Moreover, the positive effect of RP was observed in all patients but one. Conclusions Our study is the first to demonstrate that retrieval practice efficiently improves episodic memory in comparison to restudy in patients with schizophrenia. This learning strategy should therefore be considered as a useful tool for cognitive remediation programs. In this perspective, future studies might explore retrieval practice using more ecological material.